1997
DOI: 10.2527/1997.754986x
|View full text |Cite
|
Sign up to set email alerts
|

Live animal performance, carcass traits, and meat palatability of calf- and yearling-fed cloned steers.

Abstract: Two groups of Brangus steers produced by nuclear transplantation cloning were used in parallel studies investigating the impact of calf- and yearling-feeding. The first group (n = 8) were fed as calves (CF; n = 4) or yearlings (YF; n = 4) to a constant age end point of 16 mo. The second group (n = 10) were fed as calves (CF; n = 5) or yearlings (YF; n = 5) to a constant live weight end point (530 kg). When slaughtered at the same age, CF and YF steers did not differ (P > .05) in feedlot ADG, but the CF steers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Low ultimate pH in relation to increased fat depth may be due to improved animal nutrition, which increases glycogen reserves along with increasing fat cover (Warner et al 1998;McGilchrist et al 2012). Harris et al (1997) found that live weight, carcass weight, fat depth, marbling score, and initial decline in muscle pH early post mortem in carcasses from calves increased as the length of time the calves were fed a concentrate diet increased. In the present study, dark cutting (Canada B4) cattle had a mean fat depth of 8.90 ± 1.06 mm at carcass grading, well above the 7.6 mm identified by Page et al (2001), and analysis of variance results showed clearly that the mean gFD of dark cutting carcasses was not different than that of normal carcasses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low ultimate pH in relation to increased fat depth may be due to improved animal nutrition, which increases glycogen reserves along with increasing fat cover (Warner et al 1998;McGilchrist et al 2012). Harris et al (1997) found that live weight, carcass weight, fat depth, marbling score, and initial decline in muscle pH early post mortem in carcasses from calves increased as the length of time the calves were fed a concentrate diet increased. In the present study, dark cutting (Canada B4) cattle had a mean fat depth of 8.90 ± 1.06 mm at carcass grading, well above the 7.6 mm identified by Page et al (2001), and analysis of variance results showed clearly that the mean gFD of dark cutting carcasses was not different than that of normal carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…Feed intake could be depressed by acidosis (Brown et al 2000), subclinical disease, or estrus in heifers (Maltz et al 1997). Feeding an energetic diet has been reported to increase ADG and the decline in early post-mortem pH in beef (Harris et al 1997). …”
Section: Discussionmentioning
confidence: 99%
“…All carcasses from CF or YF steers were A maturity. Calves fed for 217 d have previously been reported by Harris et al (1997) to have greater marbling scores than yearlings fed for 93 d, although calves were also reported to have heavier carcasses and greater numerical yield grades. However, when these researchers fed to a constant weight endpoint, calves fed 224 d had similar carcass weights and yield grades to yearlings fed 182 d.…”
Section: Carcass Characteristicsmentioning
confidence: 97%
“…However, others have shown minimal effects of the finishing system on carcass quality grade or meat palatability (Dikeman et al, 1985a;Huffman et al, 1990). Harris et al (1997) compared cloned steers finished as calves or yearlings and reported that the calves had heavier carcasses, numerically greater yield grades, and greater quality grades when fed to an age-constant endpoint, whereas calves and yearlings fed to a constant weight yielded carcasses similar in weight and fat thickness, with no differences in quality grade. Neither endpoint in the latter study affected meat palatability between the calves and the yearlings.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ADG has been observed for older cattle placed on finishing diets compared with cattle placed directly on a finishing diet after weaning and is considered to be due to compensatory gains (Dikeman et al, 1985;Harris et al, 1997;Lunt and Orme, 1987). However, these increased gains do not improve efficiency of live-weight gain due to increased maintenance costs of the older cattle (Dikeman et al, 1985).…”
Section: Appendix Tables 1 and 2)mentioning
confidence: 99%